The Relationship between Red Blood Cell Distribution Width and Coronary Artery Lesion Severity In Acute Myocardial Infarction Patients with Non-Elevation of ST-Segment (IMA-NEST) at Haji Adam Malik Hospital - Alfuadi, T. Rifki Mirza; Mukhtar, Zulfikri; Sitepu, Andika (CoinReads Media Prima, 2024)
Introduction: Red cell distribution width (RDW), a measure of erythrocyte size variability, is associated with acute inflammation. Elevated RDW predicts adverse outcomes in cardiovascular diseases like acute myocardial infarction. This study investigated the relationship between RDW and coronary lesion severity, assessed by the SYNTAX Score, in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) undergoing coronary angiography. Methods: This retrospective analytical study included NSTE-ACS patients who underwent coronary angiography at H. Adam Malik General Hospital Medan. Baseline characteristics, laboratory parameters (including RDW), and angiography results were collected. The association between RDW and SYNTAX Score was analyzed. ROC/AUC curve analysis assessed RDW's predictive ability for coronary lesion severity, determining sensitivity and specificity. Results: In 160 patients, RDW was significantly associated with SYNTAX Score (p<0.001). TIMI score, GRACE score, and number of involved arteries also correlated with lesion severity. Conclusion: RDW is a promising predictor of coronary lesion severity in NSTE-ACS patients undergoing coronary angiography.